2018
DOI: 10.5455/medarh.2018.72.414-417
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Usefulness of Different Silicone Tubes in External Dacryocystorhinostomy

Abstract: Introduction: External dacryocystorhinostomy is a surgical procedure for the treatment of lacrimal drainage system disorders. Aim: To assess the usefulness of different silicone tubes in external dacryocystorhinostomy. Material and Methods: This study sampled 97 patients with lacrimal drainage system disorders who underwent the external dacryocystorhinostomy using two different silicone tubes. Forty one patients (Group A) underwent external d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 13 publications
0
12
0
Order By: Relevance
“…Overall evidence is limited, with only 4 relevant studies evaluating this question. One study evaluated 2 different types of silicone tubes and found that there was no significant difference in success rate between the compared groups 69 . A retrospective study evaluating silicone vs T‐tubes in endoscopic DCR suggested similar success rates 70 ; however, a prospective randomized study by Okuyucu et al 71 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall evidence is limited, with only 4 relevant studies evaluating this question. One study evaluated 2 different types of silicone tubes and found that there was no significant difference in success rate between the compared groups 69 . A retrospective study evaluating silicone vs T‐tubes in endoscopic DCR suggested similar success rates 70 ; however, a prospective randomized study by Okuyucu et al 71 .…”
Section: Resultsmentioning
confidence: 99%
“…One study evaluated 2 different types of silicone tubes and found that there was no significant difference in success rate between the compared groups. 69 A retrospective study evaluating silicone vs T-tubes in endoscopic DCR suggested similar success rates 70 ; however, a prospective randomized study by Okuyucu et al 71 comparing silicone, otologic T-tubes, and polypropylene found the success rate to be highest with silicone (87.5%), followed by polypropylene (84.4%) and T-tubes (62.5%). Spontaneous loss was a common complication with the T-tubes, and polypropylene was found to be related with orbital complications.…”
Section: Stentingmentioning
confidence: 99%
“…Many surgical techniques and instruments for stent placement have been described. The material of choice for stenting in the lacrimal system is silicone, which is generally inert within the system [8,9]. Stents implanted with in nasolacrimal system prevent adherence of the mucosal lining of the ducts during healing and maintain long term patency after removal [8,10].…”
Section: Discussionmentioning
confidence: 99%
“…The existing surgical methods include lacrimal intubation, YAG laser , external dacryocystorhinostomy (Ex-DCR) and EE-DCR [3][4]. For more than 100 years, Ex-DCR has been regarded as the "gold standard" for the treatment of chronic dacryocystitis, but it can't meet people's growing medical needs due to the shortcomings of facial skin scar, large trauma, affecting the function of "tear pump" and unable to deal with nasal complications at the same time [5][6][7]. Over the past 10 years, with the continuous improvement of endoscopic imaging system, ENT micro power system and other medical equipment, EE-DCR is highly recommended in clinic because of its incomparable advantages of Ex-DCR, such as no facial skin incision, minimally invasive and does not affect the function of "tear pump", simultaneous treatment of nasal complications, et al However, so far, the e cacy of EE-DCR has been reported differently, and its losers are not rare [8][9][10].…”
Section: Introductionmentioning
confidence: 99%